PENGARUH RISIKO KREDIT, RISIKO TINGKAT BUNGA DAN RISIKO LIKUIDITAS TERHADAP PROFITABILITAS BANK BUMN INDONESIA PERIODE 2016-2020 - Ida Ayu Sinta Dewi; I Made Hedy Wartana (Journal Research of Management, 2021)
This study aims to examine the effect of credit risk, interest rate risk and liquidity risk on the profitability of Indonesian BUMN Banks for the 2016-2020 period. This study uses associative methods and multiple linear regression analysis techniques assisted by the SPSS program, which includes validity testing, reliability testing, classical assumption testing, and hypothesis testing. Sampling using purposive sampling method, with consideration of the criteria used are government-owned banking companies successively in the study period. Based on the results of data processing, it is found that credit risk (NPL) has a negative effect on profitability (ROA) with the contribution given by the NPL variable to ROA is 33.1%. Interest rate risk (NIM) has a positive effect on profitability (ROA) with the large contribution given by the NIM variable to ROA is 59.5%. Liquidity risk (LDR) has a negative effect on profitability (ROA) with the large contribution given by the LDR variable to ROA is 12.7%.